2021
DOI: 10.1186/s12933-021-01394-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glucose disposal rate and risk of stroke and mortality in type 2 diabetes: a nationwide cohort study

Abstract: Background and aims Insulin resistance contributes to the development of type 2 diabetes (T2D) and is also a cardiovascular risk factor. The aim of this study was to investigate the potential association between insulin resistance measured by estimated glucose disposal rate (eGDR) and risk of stroke and mortality thereof in people with T2D. Materials and methods Nationwide population based observational cohort study that included all T2D patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 32 publications
(39 reference statements)
0
33
0
Order By: Relevance
“…In Penno et al’s study, subjects with eGDR < 4.14 had a hypertension prevalence of 99.5%, subjects with eGDR value between 4.15 and 5.34 also had a hypertension prevalence of 98.7%, and subjects with eGDR ≥ 5.34 had a hypertension prevalence of 52.8% [ 11 ]; In their work, they also used euglycemic hyperinsulinemic clamp test to exam the correlation between eGDR and the level of measured glucose disposal rate, the results demonstrated that the correlation of eGDR with measured glucose disposal rate was highly significant (r = 0.624, P < 0.001). In another study assessing the value of eGDR, the prevalence of anti-hypertensive therapy reached 97.9% in subjects with eGDR < 4; On the contrary, the prevalence of anti-hypertensive therapy was only 41.0% and 1.1% in subjects with eGDR 6–8 and > 8, respectively [ 13 ]. In this research, the researcher also observed a close correlation between eGDR and the results of euglycemic hyperinsulinaemic clamp (r = 0.73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Penno et al’s study, subjects with eGDR < 4.14 had a hypertension prevalence of 99.5%, subjects with eGDR value between 4.15 and 5.34 also had a hypertension prevalence of 98.7%, and subjects with eGDR ≥ 5.34 had a hypertension prevalence of 52.8% [ 11 ]; In their work, they also used euglycemic hyperinsulinemic clamp test to exam the correlation between eGDR and the level of measured glucose disposal rate, the results demonstrated that the correlation of eGDR with measured glucose disposal rate was highly significant (r = 0.624, P < 0.001). In another study assessing the value of eGDR, the prevalence of anti-hypertensive therapy reached 97.9% in subjects with eGDR < 4; On the contrary, the prevalence of anti-hypertensive therapy was only 41.0% and 1.1% in subjects with eGDR 6–8 and > 8, respectively [ 13 ]. In this research, the researcher also observed a close correlation between eGDR and the results of euglycemic hyperinsulinaemic clamp (r = 0.73).…”
Section: Discussionmentioning
confidence: 99%
“…eGDR has been demonstrated to have high precision in estimating IR compared to the euglycemic hyperinsulinemic clamp approach [12]. Additionally, published data have revealed the usefulness of eGDR in predicting cardiovascular events in diabetic patients [13][14][15][16]. However, evidence about the association between eGDR and the prevalent IHD in the general population is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that low eGDR levels are an independent predictor of increased risk of death in patients with T2DM. 6 , 7 Patients were considered to have IR when the level of eGDR value was <7.5. 8 eGDR is a continuous index, and it is simple and easy to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…2,[4][5] Lately, Alexander Zabala et al revealed that eGDR also can reflect IR in patients with type 2 diabetes. 6 Moreover, eGDR also has a predictive value. Several studies have found that low eGDR levels are an independent predictor of increased risk of death in patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of these studies showed no clinical bene t (12) suggesting that other underlying pathophysiological mechanisms of diabetes may be responsible of poor stroke recovery. IR is another main T2D-hallmark, which is also an independent risk factor for cardiovascular disease (13,14), including stroke (15). Similar to hyperglycaemia, IR has been associated with poor stroke outcome (14).…”
Section: Introductionmentioning
confidence: 99%